Discovering Shandong Art and Culture China in the Dimension of Wisdom, Beliefs, Traditional Ways of Life and Festivals - Zhang, Kai; Chandhasa, Rosjana (Journal of Ecohumanism, 2024)
With the country's continued emphasis on industry, culture and creativity industry, the cultural and creative industries on the university campus have demonstrated a strong drive of development. Shandong is a famous cultural city with a rich history with a rich material cultural heritage that is constantly inspiring for the cultural and creative industries on the university campus. This study starts from the cultural dimension of wisdom, faith, traditional way of life, and festivals and uses qualitative research methods. With a descriptive and analytical method, to explore the cultural and artistic information learning area of Shandong Province. Through comprehensive analysis and data collection, we skillfully integrate these cultural elements into the design of souvenir products, and contribute to the promotion of Shandong culture and the creation of unique cultural and creative products. The results showed that the study of information on Shandong arts and culture In the wisdom dimension The profound Confucian tradition of Shandong Province injected a unique humanistic spirit into its culture and art, which is not only reflected in the daily life philosophy of the Shandong people, but also the culture of Shandong people. In the belief dimension, Shandong province's religious and folk beliefs provide a wide area for art development, which not only strengthens the connotation of art, but also makes them more regional and cultural. In the lifestyle dimension Shandong province's unique living traditions and farming culture provide valuable materials for art development. By delving deeper into these elements, it is possible to design souvenirs with more regional characteristics and cultural values, and the traditional festival dimension. The Spring Festival and Zhoucun Xinzi Festival are not only the spiritual sustenance factor of Shandong people. Using these elements of festivals, art can be developed at a strong cultural atmosphere to meet people's pursuit of a better life. Based on the findings, it leads to strong support and guidance for the cultural and creative industry in Shandong Province, and helps promote the development of souvenir products in Shandong University.